The Influence Of Work Discipline And Organizational Culture On The Performance Of The Assidiqiyah 3 Karawang Islamic Boarding School Foundation - Hendi Supriatna; Sari Marliani; July Juliawaty (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — This research aims to determine the influence of work discipline and organizational culture on performance at the Assidiqiyah Islamic Boarding School Foundation Research method— The study employed a quantitative descriptive and verification approach, utilizing SPSS version 25 for analysis. The research was conducted at the Assidiqiyah 3 Karawang Islamic Boarding School with 55 respondents. Result— Findings indicate that work discipline scored 203, organizational culture scored 201, and performance scored 205, all classified as good. Work discipline (X1) showed no significant effect on performance (p = 0.409), while organizational culture (X2) had a significant effect (p = 0.000). Additionally, both variables together significantly influenced performance (p = 0.000). Conclusion— The study recommends organizational development for Islamic boarding school administrators to enhance work discipline, organizational culture, and performance through training or workshops, thereby optimizing management effectiveness.